Long-term changes in plaque burden and vessel remodeling in saphenous vein grafts: insights from serial intravascular ultrasound. Issue 6 (September 2016) - Wang, Bin; Yamamoto, Myong Hwa; Nand, Parma; Stewart, Jim; Webster, Mark; Gonzales, Hector; Mintz, Gary S.; Maehara, Akiko
Abstract : Supplemental Digital Content is available in the text.